Preliminary design of a submarine [compact disc] - 286041 Ghazali Sarip (Skudai : Universiti Teknologi Malaysia, 2005)
Project paper (Sarjana Muda Kejuruteraan (Mekanikal - Teknologi Marin) - Universiti Teknologi Malaysia, 2005